STRATEGI PROGRAM PEMBANGUNAN DALAM PENGENTASAN KEMISKINAN DI DESA KARYAMUKTI KECAMATAN MOOTILANGO KABUPATEN GORONTALO - Harijono Imbran; Umar Sako Baderan; Maryam Lihawa (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2020)
The objective of research was to determine the strategy of development program of poverty alleviation at Karyamukti village. The method used descriptive quantitative approach. Based on the result obtained the strategy that uses by the government at Karyamukti village are in quadrant I (S-O) aggressive, which is creating a strategy that uses strength to take advantage of opportunities. These strategy formulations include: Optimizing poverty alleviation programs carried out by the government, improving the data collection process / identification of RTM needs therefore programs are implemented on target, maximizing the use of village fund allocations in increasing human resources and capital participation that can empower communities, take advantage of the potential conditions of the supported villages by good human resources, as well as improving the socialization / training process of community groups on the potential of agriculture and other businesses / jobs run by the community.